2012
DOI: 10.1108/03074351211266793
|View full text |Cite
|
Sign up to set email alerts
|

The impact of passive investing on corporate valuations

Abstract: Over the past 20 years, a trend toward index fund investing has emerged. Currently, more mutual fund assets are indexed to the S&P 500 than any other index. Prior research on downward-sloping demand curves suggests that widespread acceptance of S&P 500 index investing may push prices of companies in the S&P 500 beyond fundamental values. This paper explores the impact of flows into S&P 500 index funds on corporate valuations. The results show that money flow into S&P 500 index funds is inflating the values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Israeli et al ( 2017 ) find that increased ETF ownership has contributed to a decline in informational efficiency as stocks move more in line with their sector and the broader market and less in line with their own earnings. Similarly, both Belasco et al ( 2012 ) and Zou ( 2019 ) find that flows into passive funds cause an increase in the price-to-fundamental ratios of the underlying stocks. The results of Coles et al ( 2022 ) reveal that the prices of stocks with a greater proportion of passive investors deviate more from a random walk, a measure of weak-form market efficiency.…”
Section: Literature Reviewmentioning
confidence: 87%
See 2 more Smart Citations
“…Israeli et al ( 2017 ) find that increased ETF ownership has contributed to a decline in informational efficiency as stocks move more in line with their sector and the broader market and less in line with their own earnings. Similarly, both Belasco et al ( 2012 ) and Zou ( 2019 ) find that flows into passive funds cause an increase in the price-to-fundamental ratios of the underlying stocks. The results of Coles et al ( 2022 ) reveal that the prices of stocks with a greater proportion of passive investors deviate more from a random walk, a measure of weak-form market efficiency.…”
Section: Literature Reviewmentioning
confidence: 87%
“…We also focus on efficiency at the market level rather than at the individual stock level, in line with Samuelson’s ( 1998 ) dictum that market efficiency may differ at the individual stock level compared to the market level. Second, our analysis sheds light on the impact of increased passive investment, as several studies have shown that increased passive investment contributes to market inefficiency (Belasco et al 2012 ; Israeli et al 2017 ; Zou 2019 ). Third, we follow the work of Coles et al ( 2022 ) by considering two different aspects of efficiency—long-range dependence and speed of adjustment—which are often examined separately in studies (Al-Yahyaee et al 2020 ; Köchling et al 2019 ) but rarely together.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…83 A similar concern has been raised with regard to index funds, which also trade rarely. 84 However, so long as any significant portion of a company's shares are owned and traded by individual or institutional shareholders outside the Fund, market prices are likely to remain at least somewhat informationally efficient. Moreover, it can be argued that the benefits associated with marginal increases in informational efficiency are small.…”
Section: Reduced Informational Efficiency In Stock Pricingmentioning
confidence: 99%